Hubungan Pengetahuan Dengan Sikap Akseptor Dalam Menangani Efek Samping KB Suntik Tiga Bulan Di Praktik Mandiri Bidan Hj. S., A. Md. Keb - Kadek Yuliari; Ni Made Dwi Mahayati; Ni Komang Lindayani (Poltekkes Kemenkes Denpasar, 2019)
Three months contraception injection, aside from having long term benefits, also has side effects such as menstruation disorder, changes in body weight, leucorrhea, galactorrhea, hair loss, acne, and other subjective disorders such as dizziness, nausea, and vomiting. This study aims to find out the correlation of knowledge and acceptors’ attitudes in handling the side effects of three months contraception injection in Hj. S., A. Md. Keb independent midwife practice. This study used a correlational analytical method with a cross-sectional approach. In this study there were 47 acceptors of three months contraception injection. The sampling technique used was purposive sampling. The bivariate analysis used Chi-Square test. The Chi-Square test result presents that there is correlation between knowledge and acceptors’ attitudes in handling the side effects of three months contraception injection in Hj. S., A. Md. Keb independent midwife practice, with p-value = 0,000 (0,05). Health workers are expected to give counseling by using decision-making tools provided so that the counseling can be well-adressed.